A physical RC network model for electro-thermal analysis of a multichip SiC power module - Li, Jianfeng; Castellazzi, Alberto; Eleffendi, Mohd Amir; Gurpinar, Emre; Johnson, Christopher Mark; Mills, Liam (IEEE, 2017)
This paper is concerned with the thermal models which can physically reflect the heat-flow paths in a lightweight three-phase half bridge, two-level SiC power module with 6 MOSFETs and can be used for coupled electro-thermal simulation. The finite element (FE) model was first evaluated and calibrated to provide the raw data for establishing the physical RC network model. It was experimentally verified that the cooling condition of the module mounted on a water cooler can be satisfactorily described by assuming the water cooler as a heat exchange boundary in the FE model. The compact RC network consisting of 115 R and C parameters to predict the transient junction temperatures of the 6 MOSFETS was constructed, where cross-heating effects between the MOSFETs are represented with lateral thermal resistors. A three-step curve fitting method was especially developed to overcome the challenge for extracting the R and C values of the RC network from the selected FE simulation results. The established compact RC network model can physically be correlated with the structure and heat-flow paths in the power module, and was evaluated using the FE simulation results from the power module under realistic switching conditions. It was also integrated into the LTspice model to perform the coupled electro-thermal simulation to predict the power losses and junction temperatures of the 6 MOSFETs under switching frequencies from 5 kHz to 100 kHz which demonstrate the good electro-thermal performance of the designed power module.